Individual differences in auditory perception predict learning of non-adjacent tone sequences in 3-year-olds - Mueller, Jutta L.; Weyers, Ivonne; Friederici, Angela D.; Männel, Claudia (Frontiers in Human Neuroscience, 2024)
Auditory processing of speech and non-speech stimuli oftentimes involves the analysis and acquisition of non-adjacent sound patterns. Previous studies using speech material have demonstrated i) children’s early emerging ability to extract non-adjacent dependencies (NADs) and ii) a relation between basic auditory perception and this ability. Yet, it is currently unclear whether children show similar sensitivities and similar perceptual influences for non-adjacent dependencies in the non-linguistic domain. We conducted an event-related potential (ERP) study with 3-year-old children using a sine-tone-based oddball task, which simultaneously tested for NAD learning and auditory perception by means of varying sound intensity. Standard stimuli were AXB sine-tone sequences, in which specific A elements predicted specific B elements after variable X elements. NAD deviants violated the dependency between A and B and intensity deviants were reduced in amplitude. Both elicited similar frontally distributed positivities, suggesting successful deviant detection. Crucially, there was a predictive relationship between the amplitude of the sound intensity discrimination effect and the amplitude of the NAD learning effect. These results are taken as evidence that NAD learning in the non-linguistic domain is functional in 3-year-olds and that basic auditory processes are related to the learning of higher-order auditory regularities also outside the linguistic domain.